Are the Symptoms of Calcific Tendinitis Due to Neoinnervation and/or Neovascularization?. (3rd February 2016) - Hackett, Lisa; Millar, Neal L.; Lam, Patrick; Murrell, George A.C.
Abstract : Background: Calcific tendinitis can be a substantial cause of pain and dysfunction in the shoulder, and the pathophysiology is unclear. Recent studies have shown a link among nerve ingrowth, neovascularization, and pain in tendinopathy. The aim of this study was to determine whether there is evidence of neoinnervation and/or neovascularization in calcific tendinitis lesions of the shoulder. Methods: At arthroscopy, ultrasound was used to identify calcium within the tendon. Samples were taken from the supraspinatus tendon adjacent to the calcific lesion (in the calcific tendinitis group, with ten patients), the torn supraspinatus tendon of patients undergoing rotator cuff repair (the rotator cuff tear group, with ten patients), and the subscapularis tendon of patients undergoing a stabilization surgical procedure (the control group, with ten patients). Biopsied tendon samples were evaluated immunohistochemically by quantifying the presence of macrophages (using CD68 and CD206), T cells (CD3), mast cells (mast cell tryptase), vascular endothelium (CD34), and peripheral nerve markers (PGP 9.5). Results: There was a twofold to eightfold increase of nerve markers, neovascularization, macrophages, M2 macrophages, and mast cells in the calcific tendinitis group compared with the rotator cuff tear group (p < 0.001) and the control group (p < 0.001). Increased nerve counts positively correlated with more frequent extreme pain (r = 0.5, p < 0.01) and with increased neovascularization (r = 0.7, p < 0.01) and counts of CD68 macrophages (r = 0.8, p < 0.01), M2 macrophages (r = 0.6, p < 0.01), and mast cells (r = 0.7, p < 0.01). Conclusions: This is the first study to show a significant increase in neovascularization and neoinnervation in calcific tendinitis lesions of the shoulder along with an eightfold increase in mast cells and macrophages. The findings are consistent with the hypothesis that, in calcific tendinitis, the calcific material is inducing a vigorous inflammatory response within the tendon with formation of new blood vessels and nerves. Clinical Relevance: This study helps to explain why calcific tendinitis is related to substantial pain in the clinical setting.